Pengaruh Penggunaan Lagu-lagu dalam Pembentukan Karakter Peserta Didik di Sekolah Dasar - Iraqi, Hana Shilfia; Lena, Mai Sri; Reviana, Fransisca Regy; Sulastri, Juliana (Lembaga Yasin AlSys, 2023)
Education plays a crucial role in shaping an individual's character, which in turn influences human behavior. In the context of elementary school education, the use of songs can be an effective way to shape the character of students. However, the influence of using songs in character formation among elementary school students has not been fully understood and scientifically examined. Therefore, this research aims to examine the impact of using songs in shaping the character of elementary school students. In this study, a qualitative approach was employed with a questionnaire as the data collection tool from 156 teachers teaching in elementary schools in Indonesia. Data were obtained through the completion of a questionnaire by teachers, consisting of 15 questions related to the use of songs in character formation. The research findings indicate that the use of songs in shaping the character of elementary school students has a positive impact, such as enhancing honesty, tolerance, and cooperation. This article will discuss the concept of character education, the role of songs as a teaching tool, and the effects of their use in shaping student character.